Sikap Inklusif - Anjar Subiantoro; Damanhuri , Damanhuri (Jurnal Multidisiplin Indonesia, 2025)
The purpose of writing this article is to: 1). Analyze the quality of hadith related to inclusive attitudes in interfaith tolerance. 2). Describe the fiqhul hadith as a guideline for implementing inclusive attitudes in society. This research was conducted using a qualitative approach with the study method. The data is obtained from the books of interpretation by previous scholars such as Tafsir Ibn Kathir and Jami' al-Bayan fii Tafsir al-Qur'an by Ath-Thabari, and from the books of modern scholars such as Muhammad Rasyid Ridha and Muhammad Hussein Adz-Dzahabi. The main message of this Hadith is the importance of interfaith tolerance and respect for diversity as a form of respect for human values. It teaches that interfaith relations should be based on mutual respect, not on differences in beliefs. Death as a spiritual reminder also emphasizes that respect for the dead is part of inclusive Islamic manners. Thus, this hadith is a relevant example for creating peace and harmony in a multicultural society.